Simplified construction of a subtracted cDNA library using asymmetric PCR. - Houge, G (Genome Research, 1993)
A novel method for the direct construction of subtracted plasmid cDNA libraries in the plasmid pBluescript is presented. Two libraries in lambda-ZAP were compared starting with general phagemid excision from both libraries. Thereafter, single-stranded (ss) plasmids from one library were subtracted with biotinylated cDNA molecules generated by asymmetric PCR on ss plasmid templates from the other library. The nonsubtracted plasmids were used to transform Escherichia coli directly, thus making a subtracted plasmid library. Preliminary data suggest that the specificity of the method is around 25%. The method is sensitive enough to detect low-abundance mRNAs. In contrast to other subtractive methods based on lambda-ZAP, the bias introduced using PCR in this case only affects the method's specificity and not its sensitivity.
10.1101/gr.2.3.204